SYSTEM OF DEVELOPING THE KNOWLEDGE OF FUTURE PHYSICAL EDUCATION TEACHERS ABOUT SPORTS TOURISM (Scientific journal of the Fergana State University, 2023)
In this article, opinions on increasing the activity of introducing educational standards based on a new approach to the training of future physical education teachers, on awakening a sense of responsibility for the chosen profession, on the development of various reforms in society are presented.